A Bi-Level Bi-Objective Mathematical Model for Stop Location in a School Bus Routing Problem. Issue 13 (2019) - Parvasi, Seyed Parsa; Tavakkoli-Moghaddam, Reza; Taleizadeh, Ata Allah; Soveizy, Mohammad
Abstract: Nowadays, due to expansion of urban areas and population growth, the number of travels in the cities has increased dramatically and private vehicles are raised as a competitor to public transportation. Hence, designing a proper transportation system to encourage individuals to use public transportation is important. In this paper, a bi-level model for a bus stop location and bus routing problem based on leader-follower games is developed. The proposed strategy in this model is based on a location-allocation-routing (LAR) strategy. The first level (i.e., leader) concerns the location and routing problem and the second level (i.e., follower) concerns the allocation problem, in which the first level is a bi-objective optimization problem. In order to solve the model, two approaches are used that are based on the explicit enumeration and hybrid methods, respectively. Finally, the proposed approaches are used to solve a number of random instance problems, whose results indicate the effectiveness of the proposed algorithms.